2016
DOI: 10.1037/drm0000038
|View full text |Cite
|
Sign up to set email alerts
|

Continuity: Knowing each other, emotional closeness, and appearing together in dreams.

Abstract: Continuity between entities in dreams and those in waking life arises from memory. In broad terms, the people a dreamer knows are associated in the dreamer's memory, and during dreaming people associated in memory tend to occur together in dreams. To obtain details, we gave a dreamer a questionnaire about whether pairs of major people know each other in waking life, and if so, how emotionally close they are. The greater the emotional closeness of a pair, the more likely the pair was to occur in a dream togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The relevant part is the participant's cognitive social network , her memory of people, and their relations (Bayer et al, 2020; Brands, 2013; Brashears & Quintane, 2015; Krackhardt, 1987; Smith et al, 2020). In previous work (Han & Schweickert, 2016), we found that the more often two people co-occurred in the dreams of our participant, the more likely the dreamer said they know each other in waking life. (We also found, not directly relevant here, that the greater the emotional closeness of two people, the more likely they were to be in a dream together.)…”
supporting
confidence: 55%
See 3 more Smart Citations
“…The relevant part is the participant's cognitive social network , her memory of people, and their relations (Bayer et al, 2020; Brands, 2013; Brashears & Quintane, 2015; Krackhardt, 1987; Smith et al, 2020). In previous work (Han & Schweickert, 2016), we found that the more often two people co-occurred in the dreams of our participant, the more likely the dreamer said they know each other in waking life. (We also found, not directly relevant here, that the greater the emotional closeness of two people, the more likely they were to be in a dream together.)…”
supporting
confidence: 55%
“…Because unusual or bizarre events occasionally occur in dreams, it is natural to wonder whether dream contents are random. Results in an earlier article (Han & Schweickert, 2016) show that contents are not random in a simple way, because the frequency of co-occurrence in dreams is correlated with emotional closeness in waking life. Here we consider the possibility that people occur in a dream together with a constrained kind of randomness.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, modern dream research is utilizing long dream series to study specific topics, for example, the effects of traveling in waking life on dream locations (Marrou & Arnulf, 2018), social networks of dream characters (Han & Schweickert, 2016), the long-term effect of applying a lucid dream induction technique (Schredl, 2013), the spiritual journey reflected in dreams (Bulkeley, 2018; Paquette, 2018), or the frequency of romantic partners still appearing in dreams years after separation (Domhoff, 2003; Schredl, 2018a).…”
mentioning
confidence: 99%